Effect of Cytokines On The In Vitro of Sweet Kaffir Lime (Citrus hystrix Dc) - Handayani, Rd. Selvy; Yunus, Ismadi; Tillah, Nadia; Handayani, Ira (Journal of Tropical Horticulture, 2020)
Sweet kaffir lime (Citrus hystrix Dc), also called "Boh Kruet Mameh" is one of Aceh's local plants, which is currently very difficult to obtain. Sweet kaffir lime is not like the ordinary kaffir lime, which tastes sour. The fruit of sweet kaffir lime has a larger size than the regular kaffir lime, sweet and sour taste, aromatic and fresh, which can be consumed as a fruit table. The problem of developing the propagation technique of sweet kaffir lime plants is the seeds' condition, which are conventionally difficult to germinate and limited in number, making it difficult to get a high-quality seed. Thus, to overcome these problems, suitable solutions to plant propagation techniques should be sought. As for the right plant propagation technique is tissue culture technology or in vitro propagation technique. This research was conducted at the Plant Tissue Culture Laboratory, Faculty of Agriculture, Malikussaleh University. The research was conducted from February to April 2018. This research used a single randomized complete design (CRD) with ten replications. The treatment is a combination of the basic media, which consists of MS0 (MS media without BAP) and MS1 (MS + BAP 4 ppm). The result showed that the adduction of 4 ppm BAP in MS media influenced the in vitro sweet kaffir lime seeds' growth. Sweet kaffir lime seeds that were given 4 ppm BAP grew buds faster with more percentage of shoot growth, the number of shoots, and a number of leaves than the seeds without BAP adduction.